Evaluation of the functional state after post-resection of radial bone surgery in the course of treatment of giant cell tumor using the MSTS and DASH scales - Szczypiór-Piasecka, Karina; Nowicka, Sandra; Antczak, Krzysztof; Mińko, Alicja (Journal of Education, Health and Sport, 2021)
Introduction: The incidence of a giant radial tumor in the distal part qualifies in third place. It is very susceptible to local recurrences, which may appear within 2-3 years of the treatment. The giant cell tumor leads to the destruction of bones along with the acquisition of surrounding tissues. Most often, the diagnosis of cancer occurs too late, due to non-characteristic symptoms. Treatment includes surgical removal of the tumor and the use of reconstruction covered by the lesion or the performance of resection with the filling of the bone defect. If surgery is not possible, doctors will administer denosumab or radiotherapy with treatment. Aims: 1) The assessment of the usefulness of MSTS and DASH scales for the examination of the functional state after onco-orthopedic surgery. 2) Characteristics of giant cell tumor treatment and rehabilitation after radial bone reconstruction surgery. 3) Development of a physiotherapy program after post-resection of radial bone surgery Material and methods: The clinical data of the patient treated in the Department of Orthopedics, Traumatology and Oncology of the Motor Organs in Szczecin were used. The patient underwent surgery to remove the tumor of the giant cell part of the distal radius with the use of arthroplasty and reconstruction of the joint. To assess the functional recovery of the upper limb, the DASH and MSTS scales were used. Data on both scales were replenished before and after surgery at 612.28 and 24 months. Results: DASH and MSTS scale, find their application in the assessment of the functional state of the hand after post-resection allograft and are a good determinant of the effects of the rehabilitation. Conclusions: 1) DASH and MSTS scales describe the functional status of patients at every stage of onco-orthopedic treatment. 2) Rehabilitation started on the first postoperative day accelerates the healing and rehabilitation process after bone reconstruction surgery.